Role of laser application in endodontic treatment: a review of literature - Abulhamayel, Abdulkader Abdulelah; Alsulami, Khalid Abdulbaqi; Alshehri, Ali Nasser; Alasmari, Abdullah Hussain; Alzahrani, Faisal Ramadan; Altayeb, Majid Abdulkader; Almane, Abdullah Ibrahim; Alshehri, Alhanouf Khaled; Alotaiby, Faisal Mohammed; Algahtani, Abdullah Mufarrih; Algthaiae, Mohammed Saeed (International Journal Of Community Medicine And Public Health, 2021)
Many applications have been previously reported that laser is used in the field of endodontics. It is used in pulp diagnosis, shaping and disinfection of the root canal, endodontic surgeries, modifying the dentin structures, pulpotomy and pulp capping. Our present study aims to review some applications of laser used in the field of endodontics. According to the evidence from current studies in the literature, vital pulp therapeutic approaches for pulpotomy can significantly lead to efficacious and bloodless outcomes by using laser for the following processes: Coagulation, vaporization, and sealing of the blood vessels with potentially sterile minute wounds with no complications. Many advantages have been previously reported for using laser within endodontic surgical procedures, such as coagulation, sterilization, selective absorption, precision, lower rates of complications as inflammation and edema, getting clean, well-sealed surgical wounds, enhanced disinfection characteristics, reduced painful sensations, decreased required sutures due to better hemostasis, and reduced bleeding. On the other hand, applying some laser modalities might not be adequately efficacious according to previous studies in the literature. We recommend that further human prospective to conduct investigations for further validation of the current evidence.